Use of azacitidine for myelodysplastic syndromes: controversial issues and practical recommendations - Kim, Yoo-Jin (Korean Society of Hematology; Korean Society of Blood and Marrow Transplantation; Korean Society of Pediatric Hematology-Oncology; Korean Society on Thrombosis and Hemostasis, 2013)
Azacitidine is recommended for patients with higher-risk myelodysplastic syndromes (MDS) who are not eligible for intensive therapy or for patients with lower-risk MDS who have thrombocytopenia or neutropenia or have anemia that is unresponsive to other therapies. However, standard treatment with azacitidine has not been optimized and many issues about the use of azacitidine remain unresolved. The use of azacitidine is expanding rapidly, but limited comparative clinical trial data are available to (i) define the optimal use of azacitidine in patients with higher-risk MDS or around the time of allogeneic hematopoietic stem cell transplantation, (ii) identify those patients with lower-risk MDS who may benefit from treatment, and (iii) guide physicians on alternative therapies after treatment failure. Increasing evidence suggests that the clinical features, prognostic factors, and cytogenetic profiles of patients with MDS in Asia differ significantly from those of patients in Western countries, so the aim of this review is to summarize the evidence and provide practical recommendations on the use of azacitidine in patients with MDS in the Republic of Korea. Evidence considered in this review is based on published clinical data and on the clinical experience of an expert panel from the acute myeloid leukemia/MDS Working Party of the Korean Society of Hematology.